Notary's Responsibility for the Denial of Signature of A Letter Under the Hand that Legalized Before A Notary - Dinda Putri yani (Authentica, 2023)
The notary is responsible for what he has made in accordance with the duties and powers that a notary must carry out. The authority of a Notary is stated in Article 15 paragraph (1) of Law No. 2 of 2014, and besides that, the authority to do authentic deeds, Article 15 paragraph (2) of Law Number 2 of 2014 concerning the Position of Notary which states that a Notary has the authority to "Authorize the signature and determine the certainty of the date of the letter under the hand by registering in a special book". With the formulation of the problem, how is the responsibility for the signature of the private agreement that has been legalized by a notary, and what is the legal force against the party who denies the signature of the private agreement that has been legalized before a notary. This research uses normative juridical methods and library research. The data used in this article uses primary, secondary, and tertiary legal materials. The results of this study show that the strength of proof of an underhand agreement that is legalized before a notary can be stronger as a means of legal protection for the parties. Article 16, paragraph 1 letter a Law No. 2 of 2014 reads, "In carrying out his position a notary must act in a trustful, honest, thorough, independent, impartial and safeguard the interests of parties related to legal actions".  Therefore, Notary must prioritize the principle of prudence and understand your rights and obligations.Keywords: Notary, Letter Under Hand, Denial.